Gender and Cultural Differences in the Relationships between Self-Esteem Contingency, Body Talk, and Body Esteem - Jounghwa Choi (MDPI AG, 2021)
This study analyzed the positive and negative body talk of male and female adolescents cross-culturally with an emphasis on the role of appearance-contingent and others’ approval-contingent self-worth. A cross-national survey in Austria, Belgium, Spain, and South Korea among 12- to 16-year-olds (982 female and 993 male) found that (1) positive body talk was positively related and negative body talk was negatively related to body esteem; (2) appearance contingency was positively related to negative body talk; (3) appearance contingency increased positive body talk among girls (except Korean girls); and (4) contingency on other’s approval increased positive body talk among boys in all four countries. Overall, gender differences were more prominent than cultural differences and positive body talk was instrumental in promoting adolescents’ body esteem.